2018
DOI: 10.3389/fnmol.2018.00133
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Wdr13 Gene Predisposes Mice to Mild Social Isolation – Chronic Stress, Leading to Depression-Like Phenotype Associated With Differential Expression of Synaptic Proteins

Abstract: We earlier reported that the male mice lacking the Wdr13 gene (Wdr13-/0) showed mild anxiety, better memory retention, and up-regulation of synaptic proteins in the hippocampus. With increasing evidences from parallel studies in our laboratory about the possible role of Wdr13 in stress response, we investigated its role in brain. We observed that Wdr13 transcript gets up-regulated in the hippocampus of the wild-type mice exposed to stress. To further dissect its function, we analyzed the behavioral and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These main signaling pathways were related to the Adcy9, Apc, Cacna1c, Camk2a, Camk2b, Camk2g, Ctnnd2, Grin2a, and Stx1a proteins. According to previous reports, Cacna1c, Camk2a, Camk2g, Grin2a, and Stx1a are all candidate genes for depression (Calabrò et al., 2019 ; Y. Kim et al., 2016 ; Mitra et al., 2018 ; Wingo et al., 2018 ; Yawalkar et al., 2018 ). The correlation of Adcy9, Apc, Camk2b, Camk2g, and Ctnnd2 with the pathological mechanisms of depression was first reported in the present work.…”
Section: Discussionmentioning
confidence: 94%
“…These main signaling pathways were related to the Adcy9, Apc, Cacna1c, Camk2a, Camk2b, Camk2g, Ctnnd2, Grin2a, and Stx1a proteins. According to previous reports, Cacna1c, Camk2a, Camk2g, Grin2a, and Stx1a are all candidate genes for depression (Calabrò et al., 2019 ; Y. Kim et al., 2016 ; Mitra et al., 2018 ; Wingo et al., 2018 ; Yawalkar et al., 2018 ). The correlation of Adcy9, Apc, Camk2b, Camk2g, and Ctnnd2 with the pathological mechanisms of depression was first reported in the present work.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, this research group showed that the lack of Wdr13 led to the up-regulated expression of multiple genes, including synaptic genes such as Syn1, Rab3a, Nrxn2, and Camk2a. Surprisingly, Wdr13 null mice demonstrate better results in the Morris water maze task of spatial memory than wild-type animals [ 17 ]. Another study indicates that a lack of WDR13 protein impairs memory and learning efficiency [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples were processed and analysis was carried out using methods described previously [ 24 ]. Data are available via ProteomeXchange with identifier PXD005644.…”
Section: Methodsmentioning
confidence: 99%